Fuzzy Production Inventory Model considering Imperfect Quality and Shortage: A Case Study in a Goat Milk SMEs - Puryani Puryani; Laila Nafisah; Nuansa Indriya Pramasthi; Apriani Soepardi; Mohammad Chaeron (OPSI, 2022)
Goat milk powder is one of the perishable processed products. The decreasing quality of goat milk powder can cause financial losses to the company if not regulated properly. So far, the company is also faced with the problem of consumer demand uncertainty. When demand for powdered goat's milk is high, the company experiences stockout but can be overcome by backorder. When demand is low, there will be overstock. Overstock conditions, in addition to causing high holding costs, are also at risk of product quality degradation or expiration. In this study, an inventory model of goat milk powder was developed that considers the uncertainty of demand, product quality, and backorder to determine the optimal production quantity so that the total inventory cost incurred is minimum. The basic model used is economic production quantity. Uncertainty in demand and the percentage of products declining in quality is approached using a triangular fuzzy. While the defuzzification technique used is signed distance.